1991
DOI: 10.21236/ada234503
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Enlisted Women in Navy Work Centers

Abstract: Public eporting burden for this collection of information is esimated to average I hour per respomne including the time for reviewing instructions, searching existing data source. gatring and maintaining the data needed, and completing and reviewing the collection of information. Send cormnents regarding this burden estinate or any other aspect of this collection of inormstion, including suggetions for reducing this burden, to Washington Headquarters Services Directorate for Information Operatiom and Reports. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
1
3
0
Order By: Relevance
“…Specifically, pregnant ADSMs faced both overt and covert messages about being less disciplined, lazy, weak, and deceitful. These experiences are congruent with rhetoric seen in newspaper headlines and research occurring about women in the military during the Gulf War (Thomas et al, 1991). It appears that negative attitudes toward pregnancy in the military have remained stable over the past 30 years.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Specifically, pregnant ADSMs faced both overt and covert messages about being less disciplined, lazy, weak, and deceitful. These experiences are congruent with rhetoric seen in newspaper headlines and research occurring about women in the military during the Gulf War (Thomas et al, 1991). It appears that negative attitudes toward pregnancy in the military have remained stable over the past 30 years.…”
Section: Discussionsupporting
confidence: 72%
“…In 1978, a study on women in the Army found pregnancy led enlisted women ADSMs to miss twice as much work as men, which negatively affected unit morale (Army Administrators, 1978). Another study found Navy commanders made references to women soldiers “deliberately becoming pregnant to avoid work or service altogether” (Thomas et al, 1991, p. 14). For example, newspaper headlines during the Persian Gulf War read “Pregnancy Kept GI Jill Out of War; A Camouflage Baby Boom?…”
Section: Military Culturementioning
confidence: 99%
“…Dietrich (1988) profiled a female soldier with orders to report to a remote Indian Ocean Naval base who, as a result, was “desperately trying to get pregnant” (p. A3). According to a presidential commission ( The presidential commission , 1992), pregnancy accounted for 47% of all female nondeployments during the Gulf War; a study of Naval pregnancy included commanders’ anecdotal references to soldiers deliberately becoming pregnant to avoid work or service altogether (Thomas, Thomas, & McClintock, 1991). This said, in the early 1980s (the period of our analysis), onerous and dangerous overseas postings were fewer than they have subsequently become.…”
Section: Introductionmentioning
confidence: 99%
“…They've locked us down, so what else is there to do?” (Kennedy, 1996, p. 16). In 1990, 13% of Naval women at sea were transferred because of pregnancy; fewer than half were married, compared with three fourths of pregnant Naval women on land duty (Thomas et al, 1991; Thomas & Thomas, 1992). Thus, one variant of the argument relating exposure to fertility is that the close proximity of unmarried women to same‐age men creates the prospect for sexual activity, leading to unplanned pregnancies (Hoiberg & White, 1992).…”
Section: Introductionmentioning
confidence: 99%